Successful outcome of kleibsella necrotising fasciitis in an immunocompromised child with conservative measures - Greeshma Rajeev; Adarsh Kancharla; Latha M. Sneha; Prakash Agarwal (Pediatric Review: International Journal of Pediatric Research, 2019)
Necrotizing soft tissue infections (NSTIs), are rare, very rapidly progressing disease of superficial fascia and subcutaneous cellular tissue. They are considered as secondary infections as they develop from an initial break down of skin integrity due to trauma or surgery. There is significant local tissue destruction causing grave morbidity and long-term sequelae. NSTIs are rare in children and the predisposing factors are skin damage due to trauma, diabetes, malnutrition and immunosuppression. Broad spectrum antibiotics, wide surgical debridement and supportive care are the standard treatment options. Diagnostic delays are common as the initial signs and symptoms mimics cellulitis or abscess. The diagnostic challenges in immunocompromised host are due to the facts that : i) infections are caused by diverse organisms that are usually not considered pathogens in healthy hosts; ii) infections of soft tissue might be a part of a bigger systemic infection; iii) immune deficiency masks the clinical signs. We report a case of successful outcome with nonsurgical management of necrotizing fasciitis in a boy with newly diagnosed Acute lymphoblastic anemia. He developed Klebsiella Necrotizing Fasciitis (NF) in the first week of induction therapy and his wound healed without surgical debridement or reconstructive measures, due to the high index of suspicion, early diagnosis and adequate intervention.